ANALISIS PENERAPAN KESELAMATAN DAN KESEHATAN KERJA (K3) PADA UNIT LAUNDRY DI RUMAH SAKIT JIWA MUTIARA SUKMA - Laela Kamila Suryani; Muhammad Habibullah Aminy; Slamet Mardiyanto Rahayu; Lale Ajeng Khalifatun Wardani; Wahyu Aprilyaningsih (LPPM, Akademi Administrasi Rumah Sakit Mataram, 2025)
This study aims to analyze the implementation of Occupational Safety and Health (OSH) in the laundry unit at Rumah Sakit Jiwa Mutiara Sukma. The research employed a descriptive qualitative approach through observation, interviews, and document review to assess compliance with applicable OSH guidelines. The results indicate that OSH implementation has generally been carried out in a structured manner, as evidenced by the establishment of a dedicated Hospital OSH unit (K3RS) responsible for monitoring and controlling OSH activities throughout the hospital. The OSH management system in the laundry unit has been implemented through annual risk identification, the use of personal protective equipment (PPE), and routine education for workers. Work procedures have been standardized through established standard operating procedures (SOPs), which are implemented adequately and supported by the Infection Prevention and Control (IPC) team in linen sorting processes. Furthermore, the implementation of OSH in terms of safety, health, and work environment demonstrates the hospital’s commitment to protecting workers from both physical and biological hazards, strengthened by periodic medical check-ups and vaccination programs. In conclusion, the implementation of OSH in the laundry unit has been carried out systematically in accordance with established guidelines and has contributed positively to creating a safe and healthy working environment.